Tuning Biochar Properties via Partial Gasification: Facilitating Inorganic Nutrients Recycling and Altering Organic Matter Leaching - Liaw, Sui Boon; Wu, Hongwei (American Chemical Society, 2015)
This study reports a systematic study on the potential of employing partial gasification at low conversions for tuning biochar for better properties and facilitating the recycling of inorganic nutrient species. The raw biochars were prepared from mallee wood and leaf at fast pyrolysis at 500 °C (a temperature pertinent to bio-oil production) and subsequent tuning via partial steam gasification at 725 °C and low conversions (5 and 10% on a carbon basis). The favorable structure tuning is achieved at the expense of 8-23% carbon, which would otherwise be available for sequestration during biochar application in soil. The development of the pore structure and transformation of the chemical forms of inorganic nutrient species as a result of partial gasification increase the leachability of the inorganic nutrient species in biochars via both water and Mehlich I solution. In addition, <1.5% of the organic matter in raw and tuned biochar is water-soluble. The leaching of water-soluble organic matter from the tuned biochars after re-pyrolysis and partial gasification (but absent in the same biochars after re-pyrolysis) suggests that partial gasification increases the accessibility of organic matter trapped in closed or blocked pores formed during pyrolysis. While some aromatic compounds can be leached from the raw biochar via solvent, no aromatic compounds are detected in the leachates from the tuned biochars. The tuning of biochar via partial gasification also improves the leaching kinetics of the inherent inorganic nutrient species. The overall recyclability of the inorganic nutrient species in the raw and tuned biochar shows that tuning biochar via partial gasification can be an effective strategy for facilitating the recycling of the inherent nutrient species in biochar.